\(\sqrt{m+2\sqrt{m-1}-\sqrt{m-2\sqrt{m-1}}}\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

21 tháng 9 2018

DKXD: m\(\ge1\)

TA CÓ:

A= \(\sqrt{\sqrt{m+2\sqrt{m-1}-\sqrt{m-2\sqrt{m-1}}}}\)

\(=\sqrt{\left(\sqrt{m-1}+1\right)-\left(\sqrt{m-1}-1\right)}\)

\(=\sqrt{2}\)

21 tháng 9 2018

\(m\ge1\)

\(\sqrt{\sqrt{m+2\sqrt{m-1}}-\sqrt{m-2\sqrt{m-1}}}\)

\(=\sqrt{\sqrt{m-1+2\sqrt{m-1}+1}-\sqrt{m-1-2\sqrt{m-1}+1}}\)

\(=\sqrt{\sqrt{\left(\sqrt{m-1}+1\right)^2}-\sqrt{\left(\sqrt{m-1}-1\right)^2}}\)

\(=\sqrt{\sqrt{m-1}+1-|\sqrt{m-1}-1|}\) 

Xet \(m\ge2\)

\(A=\sqrt{\sqrt{m-1}+1-\sqrt{m-1}+1}=\sqrt{2}\)

Xet \(1\le m< 2\)

\(A=\sqrt{\sqrt{m-1}+1+\sqrt{m-1}-1}=\sqrt{2\left(m-1\right)}\)

29 tháng 6 2017

b)\(\sqrt{m+2\sqrt{m-1}}+\sqrt{m-2\sqrt{m-1}}\)

\(\Leftrightarrow\sqrt{m-1+2\sqrt{m-1}+1}+\sqrt{m-1-2\sqrt{m-1}+1}\)

\(\Leftrightarrow\sqrt{\left(\sqrt{m-1}+1\right)^2}+\sqrt{\left(\sqrt{m-1}-1\right)^2}\)

\(\Leftrightarrow\sqrt{m-1}+1+\sqrt{m-1}-1\Leftrightarrow2\sqrt{m-1}\)

29 tháng 6 2017

Câu 1 phá từng lớp ra :VD\(9+4\sqrt{2}\) =\((\sqrt{2}+2)^2\)

Câu 2:m+2\(\sqrt{m-1}\) =m-1+1+2\(\sqrt{m-1}\) =\((\sqrt{m-1} -1)^2 \)

5 tháng 7 2018

\(\text{a) }\sqrt{13+30\sqrt{2+\sqrt{9+4\sqrt{2}}}}\\ =\sqrt{13+30\sqrt{2+\sqrt{8+1+4\sqrt{2}}}}\\ =\sqrt{13+30\sqrt{2+\sqrt{\left(\sqrt{8}+1\right)^2}}}\\ =\sqrt{13+30\sqrt{2+\sqrt{8}+1}}\\ =\sqrt{13+30\sqrt{\left(\sqrt{2}+1\right)^2}}\\ =\sqrt{13+30\sqrt{2}+30}\\ =\sqrt{43+30\sqrt{2}}\\ =\sqrt{25+18+30\sqrt{2}}\\ =\sqrt{\left(5+\sqrt{18}\right)^2}\\ =5+3\sqrt{2}\)

\(\text{b) }\sqrt{m+2\sqrt{m-1}}+\sqrt{m-2\sqrt{m-1}}\\ =\sqrt{m-1+2\sqrt{m-1}+1}+\sqrt{m-1-2\sqrt{m-1}+1}\\ =\sqrt{\left(\sqrt{m-1}+1\right)^2}+\sqrt{\left(\sqrt{m-1}-1\right)^2}\\ =\sqrt{m-1}+1+\sqrt{m-1}-1\\ =2\sqrt{m-1}\)

3 tháng 7 2015

\(\sqrt{m+2\sqrt{m-1}}+\sqrt{m-2\sqrt{m-1}}\)

=\(\sqrt{\left(\sqrt{m-1}\right)^2+2\sqrt{m-1}+1}+\sqrt{\left(\sqrt{m-1}\right)^2-2\sqrt{m-1}+1}\)

=\(\sqrt{\left(\sqrt{m-1}+1\right)^2}+\sqrt{\left(\sqrt{m-1}-1\right)^2}\)

=\(\sqrt{m-1}+1+\sqrt{m-1}-1=2\sqrt{m-1}\)

25 tháng 7 2019

\(\text{Câu 1: Sửa đề}\)

\( a)M = \left( {1 - \dfrac{{4\sqrt x }}{{x - 1}} + \dfrac{1}{{\sqrt x - 1}}} \right):\dfrac{{x - 2\sqrt x }}{{x - 1}}\\ M = \left[ {1 - \dfrac{{4\sqrt x }}{{\left( {\sqrt x - 1} \right)\left( {\sqrt x + 1} \right)}} + \dfrac{1}{{\sqrt x - 1}}} \right].\dfrac{{\left( {\sqrt x - 1} \right)\left( {\sqrt x + 1} \right)}}{{x - 2\sqrt x }}\\ M = \left[ {1 + \dfrac{{ - 4\sqrt x + \sqrt x + 1}}{{\left( {\sqrt x - 1} \right)\left( {\sqrt x + 1} \right)}}} \right].\dfrac{{\left( {\sqrt x - 1} \right)\left( {\sqrt x + 1} \right)}}{{x - 2\sqrt x }}\\ M = \left[ {1 + \dfrac{{ - 3\sqrt x + 1}}{{\left( {\sqrt x - 1} \right)\left( {\sqrt x + 1} \right)}}} \right].\dfrac{{\left( {\sqrt x - 1} \right)\left( {\sqrt x + 1} \right)}}{{x - 2\sqrt x }}\\ M = \dfrac{{\left( {\sqrt x - 1} \right)\left( {\sqrt x + 1} \right) - 3\sqrt x + 1}}{{\left( {\sqrt x - 1} \right)\left( {\sqrt x + 1} \right)}}.\dfrac{{\left( {\sqrt x - 1} \right)\left( {\sqrt x + 1} \right)}}{{x - 2\sqrt x }}\\ M = \sqrt x \left( {\sqrt x - 3} \right).\dfrac{1}{{x - 2\sqrt x }}\\ M = \dfrac{{x - 3\sqrt x }}{{x - 2\sqrt x }} \)

\( b)M = \dfrac{1}{2} \Rightarrow \dfrac{{x - 3\sqrt x }}{{x - 2\sqrt x }} = \dfrac{1}{2}\\ \Leftrightarrow 2\left( {x - 3\sqrt x } \right) = x - 2\sqrt x \\ \Leftrightarrow 2x - 6\sqrt x = x - 2\sqrt x \\ \Leftrightarrow - 4\sqrt x = - x\\ \Leftrightarrow 16x = {x^2}\\ \Leftrightarrow 16x - {x^2} = 0\\ \Leftrightarrow x\left( {16 - x} \right) = 0\\ \Leftrightarrow \left[ \begin{array}{l} x = 0\\ 16 - x = 0 \end{array} \right. \Leftrightarrow \left[ \begin{array}{l} x = 0\\ x = 16 \end{array} \right. \)

25 tháng 7 2019

\(\text{Câu 2}:\)

\( a)\sqrt {49x - 98} - 14\sqrt {\dfrac{{x - 2}}{{49}}} = 3\sqrt {x - 2} + 8\left( {x \ge 2} \right)\\ \Leftrightarrow 7\sqrt {x - 2} - 3\sqrt {x - 2} = 8 + 14\sqrt {\dfrac{{x - 2}}{{49}}} \\ \Leftrightarrow 4\sqrt {x - 2} = 8 + 14\sqrt {\dfrac{{x - 2}}{{49}}} \\ \Leftrightarrow 4\sqrt {x - 2} = 8 + 14\dfrac{{\sqrt {x - 2} }}{7}\\ \Leftrightarrow 4\sqrt {x - 2} = 8 + 2\sqrt {x - 2} \\ \Leftrightarrow 4\sqrt {x - 2} - 2\sqrt {x - 2} = 8\\ \Leftrightarrow 2\sqrt {x - 2} = 8\\ \Leftrightarrow \sqrt {x - 2} = 4\\ \Leftrightarrow x - 2 = 16\\ \Leftrightarrow x = 16 + 2 = 18 \text{(thỏa mãn điều kiện)} \)